2015
DOI: 10.5603/fm.a2018.0065
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric characteristics of the optic canal and the optic nerve

Abstract: The optic nerve (ON), a major component of the visual system, is divided into four segments: the intrabulbar (IB), the intraorbital (IO), the intracanalicular (ICn) and the intracranial (ICr). The ICr ends with the two nerves partially decussating in the optic chiasm (OCh). The purpose of this study is to provide a detailed description of the dimensions of the OC (the diameter and the surface area of its foramina and the central segment, as well as the length of the OC and the thickness of its walls) as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 20 publications
8
8
0
Order By: Relevance
“…In this study, a significant difference was not found between right and left diameter measurements, similar to most studies in the literature. 22,23,34,3638 However, Kumar et al 1 observed that the right aperture height (5.14 ± 0.73 mm) was greater compared to the left (4.82 ± 0.77 mm). Moreover, Kalthur et al 41 found that the right aperture diameters (height: 3.67 ± 0.82 mm, width: 4.68 ± 0.86 mm) was greater compared to the left (height: 3.54 ± 0.71 mm, width: 4.51 ± 0.79 mm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a significant difference was not found between right and left diameter measurements, similar to most studies in the literature. 22,23,34,3638 However, Kumar et al 1 observed that the right aperture height (5.14 ± 0.73 mm) was greater compared to the left (4.82 ± 0.77 mm). Moreover, Kalthur et al 41 found that the right aperture diameters (height: 3.67 ± 0.82 mm, width: 4.68 ± 0.86 mm) was greater compared to the left (height: 3.54 ± 0.71 mm, width: 4.51 ± 0.79 mm).…”
Section: Discussionmentioning
confidence: 99%
“…lww.com/SCS/D892) (mean data range for the aperture height: 3.60-5.17 mm, and for the aperture width: 4.59-7.38 mm). 1,22,[31][32][33][34][35][36][37][38][39][40][41] Prado et al 36 measured the aperture diameter in fetuses (right: 3.76 mm, left: 3.79 mm), children (right: 4.67 mm, left: 4.72 mm), and adults (right: 5.24 mm, left: 5.43 mm), and declared that the width increased from fetal period to adult period. In addition, Ten et al 22 measured the aperture diameters (width: 6.12 ± 0.84 mm, height: 4.35 ± 0.64 mm) in pediatric subjects aged between 1 and 20 years, and observed that its diameters did not alter from the prepubescent period.…”
Section: Discussionmentioning
confidence: 99%
“…It means that the longer extent was correlated with the involvement of intracanalicular optic nerve. Intracanalicular optic nerves are surrounded by bony structures; even a small amount of swelling of the tissue may cause optic nerve compression because of vulnerability to compression, owing to space limitations in the canal (23,24). Therefore, further studies should be needed to certify the effect of lengths and location of lesions, separately.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore important to consider the lengths of the superior and inferior orbital depths during deep orbit surgical operations in order not to damage the optic nerve and associated vessels (Huanmanop et al;2007). The aim of study was to collect data of bony orbits from our local population because racial differences exist as shown by previous studies (Yoon et al;2016) and (Radunovic M et al;2018). As we lack data from our region in Pakistan, this study will be helpful in various techniques of anesthesia and in maxillofacial, orbital and plastic surgical procedures to reduce the risk of various complications…”
Section: Introductionmentioning
confidence: 99%